Transformational Leadership in Strengthening the Teaching Factory (TEFA) Ecosystem and Its Impact on the Quality of Vocational High School Graduates: A Systematic Literature Review - Handepi, Nogi; Giatman, M.; Sukardi, Sukardi (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
Vocational education in Indonesia faces fundamental challenges in bridging the competency gap between Vocational High School (SMK) graduates and industry standards. The Teaching Factory (TEFA) learning model has been identified as a strategic solution; yet its implementation often encounters obstacles due to suboptimal managerial and leadership factors. This study aims to systematically analyze the role of school principals' transformational leadership in strengthening the TEFA ecosystem and its impact on improving SMK graduate quality. Using the Systematic Literature Review (SLR) method based on PRISMA framework, this study examined 21 selected articles from SINTA-accredited journals (SINTA 2, 3, and 4) published between 2020–2025. The analysis reveals five key findings: (1) Transformational leadership functions as a catalyst in transforming school culture from purely academic to industrial culture; (2) Four dimensions of transformational leadership have differential contributions to teacher innovation and TEFA ecosystem formation, with Inspirational Motivation showing the strongest empirical support (86%); (3) Strengthening the TEFA ecosystem requires professional management of production units with corporate-like management principles; (4) TEFA implementation supported by transformational leadership has significant positive correlation with increases in graduates' hard skills, soft skills, and employability; (5) Integration of transformational leadership with digital competence becomes a prerequisite in the context of Society 5.0 and Industry 4.0 Revolution. This study recommends strengthening SMK principals' managerial capacity through entrepreneurship-based leadership development programs and production unit management. Practical implications include recruitment and training policies for school principals that prioritize transformational leadership competence and business literacy.